Perceived negative impact of caregiving demands in parents of individuals with autism spectrum disorders from 9 to 25 years of age - Christopher, Kourtney; Tafolla, Maira; Sterrett, Kyle; Elias, Rebecca; Lord, Catherine (Research in autism spectrum disorders, 2023)
Caregivers of autistic individuals often report higher levels of perceived negative impact of caregiving. We know very little about the trajectories of caregivers perceived negative impact related to caregiving demands over time in autism. The aim of this study was to identify trajectories of perceived negative impact related to parenting of caregivers of autistic individuals and other developmental delays from childhood through emerging adulthood (n = 209). We also explored the factors that predict trajectories of caregiver perceived negative impact including the characteristics of the autistic individuals at age 9 (i.e., social affect, restricted and repetitive behaviors, irritability, hyperactivity, daily living skills and cognitive ability) and caregivers’ race, education, social support, and study site. Latent class growth modelling yielded three negative impact of caregiving classes: (1) a low impact class that decreased over time (n = 68, 32.54 %), (2) a medium impact class that increased in negative impact during adolescence and decreased in emerging adulthood (n = 98, 46.98 %), and (3) a high impact class that decreased over time (n = 43, 20.57 %). Across all classes, reductions in negative impact of caregiving over time were reported in emerging adulthood, but the high and medium impact groups were still elevated in comparison to the low impact class at the last timepoint. Caregivers of children with less irritability and parent-reported restricted and repetitive behaviors were more likely to belong to the low negative impact group. Caregivers who were African American, had lower educational attainment and those with social support were more likely to belong to the low negative impact group. These findings highlight the importance of continued support for caregivers of autistic individuals over time. The influence of race and education on levels of caregiver perceived negative impact of caregiving are discussed further. •Various trajectories of perceived negative impact in caregivers of autistic people.•Family and individual characteristics influence perceived negative impact.•Negative impact decreases in from early adolescence to emerging adulthood.•Perceived negative impact changes but remains elevated from childhood to adulthood.